2017
DOI: 10.1093/plankt/fbx062
|View full text |Cite
|
Sign up to set email alerts
|

Resting eggs in free living marine and estuarine copepods

Abstract: Marine free living copepods can survive harsh periods and cope with seasonal fluctuations in environmental conditions using resting eggs (embryonic dormancy). Laboratory experiments show that temperature is the common driver for resting egg production. Hence, we hypothesize (i) that seasonal temperature variation, rather than variation in food abundance is the main driver for the occurrence of the resting eggs strategy in marine and estuarine copepod species; and (ii) that the thermal boundaries of the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 108 publications
1
32
0
Order By: Relevance
“…This phenomenon is identical with the recent report, where Holm et al. () revealed that copepod dormant eggs production is highly variable among individuals and populations. In addition, a diversity of diapausing eggs production has been well demonstrated in different populations of widely distributed calanoid copepods Eurytemora affinis and A. tonsa (Ban, ; Drillet, Goetze, Jepsen, Højgaard & Hansen, ; Drillet, Jepsen, Højgaard, Jørgensen & Hansen, ; Glippa, Alekseev & Souissi, ), and it is considered as a function of genetic differentiation or micro‐evolutionary divergence due to geographic isolation (Drillet, Jepsen, et al., ; Glippa et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon is identical with the recent report, where Holm et al. () revealed that copepod dormant eggs production is highly variable among individuals and populations. In addition, a diversity of diapausing eggs production has been well demonstrated in different populations of widely distributed calanoid copepods Eurytemora affinis and A. tonsa (Ban, ; Drillet, Goetze, Jepsen, Højgaard & Hansen, ; Drillet, Jepsen, Højgaard, Jørgensen & Hansen, ; Glippa, Alekseev & Souissi, ), and it is considered as a function of genetic differentiation or micro‐evolutionary divergence due to geographic isolation (Drillet, Jepsen, et al., ; Glippa et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…where they remain for months to years until hatching during favorable conditions (Holm et al, 2017). This "egg bank" enables species to adapt to seasonal variability, helps to smooth the effects of variable reproduction across years, and facilitates the coexistence of diverse species and genotypes (Hairston, 1996;Marcus et al, 1994).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Embryonic Dormancy-Copepod Resting Eggs Engel and Hirche (2004) reported at least 49 marine and estuarine species that produce resting eggs; however, a recent review by Holm et al (2018) revised this to 42 species by excluding anecdotal observations and including only welldocumented production of resting eggs. The embryonic diapause trait originated in the most ancient Calanoida during the Triassic or even Permian according to Alekseev and Starobogatov (1996).…”
Section: Copepods Exhibit Flexible Life Cyclesmentioning
confidence: 99%